Microenterprises and multiple bank relationships: Evidence from a survey among professionals - Doris Neuberger; Solvig Räthke (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
An overview of previous evidence about relationship banking to SMEs shows that multiple banking relationships prevail even at small firms, but there is hardly evidence on the number of banking relationships held by micro firms. To close this gap, we use data from a survey conducted among professionals in Germany in 2002. Being self-employed persons acting in the services sector, professionals are mostly informationally opaque micro firms. To explain the number of their banking relationships, we investigate characteristics of the firm and its loan demand, characteristics of the housebank and its relationship to the borrower, and variables of bank market structure and regulation. Consistent with the theory of asymmetric information, we find that these firms hold a small number of bank relationships, which increases in firm size and age. An increase in the duration or importance of the housebank relationship does not induce multiple banking relationships as predicted by the hold-up theory. Professionals rather tend to hold multiple banking relationships to increase their credit availability and finance larger loans. The type of the housebank and local banking market concentration do not seem to matter. All in all, the results indicate that multiple bank relationships help to overcome credit rationing.
Keywords: G21; G32; 330